An Assessment of the Cues College Students Interpret From a Sexual Partner to Determine They Are Refusing - Marcantonio, Tiffany L. (Journal of interpersonal violence, 2022)
The purpose of this study was to assess the cues college students use to determine a sexual partner is refusing vaginal-penile sex (i.e., refusal interpretations). As a secondary aim, we explored the influence of item wording (not willing/non-consent vs refusal) on college students? self-reported refusal interpretations. A sample of 175 college students from Canada and the United States completed an open-ended online survey where they were randomly assigned to one of two wording conditions (not willing/non-consent vs refusal); students were then prompted to write about the cues they used to interpret their partner was refusing. An inductive coding procedure was used to analyze open-ended data. Themes included explicit and implicit verbal and nonverbal cues. The refusal condition elicited more explicit and implicit nonverbal cues than the not willing/non-consent condition. Frequency results suggested men reported interpreting more explicit and implicit verbal cues. Women reported interpreting more implicit nonverbal cues from their partner. Our findings reflect prior research and appear in line with traditional gender and sexual scripts. We recommend researchers consider using the word refusal when assessing the cues students interpret from their sexual partners as this wording choice may reflect college students? sexual experiences more accurately.